Dilema Komersialisasi Pengetahuan Tradisional Dalam Sistem Hukum Indonesia: Antara Perlindungan Dan Pembagian Manfaat - Siddiq, Miqdad Abdullah (UI Scholars Hub, 2018)
The commercial utilization of Traditional Knowledge is intended for the benefit of the national economy, especially for the welfare of indigenous peoples as the owners of Traditional Knowledge. Indonesia, which has many indigenous peoples, also has a widevariation of Traditional Knowledge. With the opening of opportunities for parties other than the owners of Traditional Knowledge to utilize the Traditional Knowledge, setting the regulatory governing the commercialization of Traditional Knowledge becomes increasingly strategic. So that the management of the protectionfor Traditional Knowledge in Indonesia has become a very urgent need. In the absence of adequate Traditional Knowledge protection regulations, Traditional Knowledge-related violations will continue to occur. In addition, the utilization of Traditional Knowledge related to its commercial use shall establish the principle of equitable sharing of benefit to indigenous peoples as the original owners of such Traditional Knowledge. Benefit sharing can be represented in the form of monetary compensation and non-monetary compensation.